Usefulness of Achillea Milefolium as healing topical agent in treating thermal burn (histological comparative study in Westar rats) (Mustansiria Dental Journal, 2023)
Background: Wound can be defined as any disruption or any damage in tissue or anatomical function or structure. Achillea Milefolium extract has medicinal benefits for tissues, including the ability to repair wounds and act as an antioxidant and anti-inflammatory.Aim of the study: The purpose of the study was to determine how Achillea Milefolium affected the healing of burn wounds.Material and Methods: Twenty male rats had their right and left cheeks burned (aged around two months with average weight about 300 to 350 g). Rats with burned skin were assigned randomly into two equal groups. Achillea milefolium solution was applied locally to the burned areas on the right side once daily (experimental group), while the left part left without any kind of treatment as control group. Five rats from each group were euthanized after five and ten days, and tissue samples were taken from the burnt areas that had been injured for histological analysis.Results: In comparison to the control group, rats given Achillea milefolium treatment had faster wound healing, according to histopathological analysis. Re-epithelialization, closure of the wound, and the infiltration of inflammatory cells were signs that the wound was healing.Conclusions: Application of Achillea milefolium solution locally promotes healing of burn wounds.